Total organic carbon in Arctic Ocean surface sediments - Ruediger Stein (PANGAEA, 2026)
This dataset includes TOC values from 3521 surface sediment stations used to produce the distribution map shown in Figure 5-15 of Stein (2008). Distribution map of organic carbon content in Arctic Ocean surface sediments. Map has been compiled using the Ocean Data View software (Schlitzer, 2001) and data from Boström et al. (1984), Hebbeln and Berner (1993), Stein et al., 1994, Naidu et al. (2000, 2004), Stein and Fahl (2000), Stein et al., (2003), Birgel and Stein (2004), Macdonald et al. (2004), Petrova et al. (2004), Vetrov and Romankevich (2004), and Kierdorf (2006), and Pavlidis (www.pangaea.de/search?q=Pavlidis).
In: Stein, R (2026): Clay and heavy minerals and total organic carbon in Arctic Ocean surface sediments – Data tables to distribution maps of Stein (2008) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.992951